Hubungan kepuasan pelayanan makanan rumah sakit dan asupan makanan dengan perubahan status gizi pasien ( Studi di RSUD Sunan Kalijaga Kabupaten Demak ) - Semedi, Pujo; Kartasurya, Martha Irene; Hagnyonowati, Hagnyonowati (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2013)
Abstract Background: Several studies have shown that hospital patients tend to have a decrease in their nutritional status during their hospitalization period. Patient satisfactions to the food service in the hospital will influence the food intake and this food intake will have an effect on the nutritional status. Objectives: To analyze the correlation between patients satisfaction to the hospital food service, food intake, and the change in the nutritional status of patients in Sunan Kalijaga Hospital, Demak.Method: This study was an analytic observational research with a cross sectional approach. This study was done on 85 subjects of inpatients in the first, second, and third classess of Sunan Kalijaga Hospital. The dependent variable was the change in nutritional status. The independent variables were the patient satisfactions to the hospital food service and food intake. Data on patient satisfactions to the hospital food service were collected by interviews using structured questionnaires. Data on food intake of the hospital food were collected by Comstock method of the food remains after the consumption, while on food intake from of hospital were collected by 3 x 24 hour recall. The changes in nutritional status were measured by the change in BMI. Data were analyzed by correlation tests.Result: Most of subjects (97,3%) satisfied to the foodservice in the hospital. The average energy adequacy level of the hospital was 76,5 ± 9,4% and protein adequacy level was76,1± 10,3%. The average energy adequacy of out hospital food was 6,5± 6,7% and protein adequacy level was 6,7± 6,9%. The average BMI at first day were 20,0 ± 3,4 kg/m2 and at the end of hospitalization were 19,7± 3,4 kg/m2. The average decreased in this study was 0,3 ± 0,2 kg/m2. There was correlation between foodservice satisfaction and the energy (p =0,009) and protein adequacy level (p=0,015). There were correlation between food intake and energy (p= 0,0001) and protein adequacy level(p= 0,038) to the change in subjects nutritional status. There was a correlation between hospital foodservice satisfaction and the change in nutritional satisfaction (p = 0,003).Conclusion: The higher level of hospiotal foodservice satisfaction, the higher of food intake and result in smaller decrease of the nutritional status Keywords : hospital, foodservice,satisfaction, nutrition